Filozofická interpretácia Sokratovho daimonia v zlomkoch Terpsiona a Eukleida z Megár - František Škvrnda (Filozofia)
The main aim of the study is to analyze selected fragments of the Megarics dealing with Socrates’ daimonion and the double deity (duplex genius). The first part of the study analyzes the doxographical evidence about Terpsion of Megara. The second part of the study reconstructs Terpsion’s purported theory of Socrates’ daimonion from the dialogue of Plutarch De genio Socratis. The third part of the study analyzes the only extant fragment of Euclid of Megara about daimones and dieties. In the conclusion we formulate the hypothesis that the traces and features of the Megaric interpretation of the daimonion are to some extent also present in various Socratic philosophers as well as schools, ranging from Plato and the Cynics to Aristotle and the Stoics, and that it represents a philosophical reinterpretation of traditional forms of religiosity and superstition.